Landscape archetypes for ecological classification and mapping: The virtue of vagueness. (February 2017) - Cullum, Carola; Brierley, Gary; Perry, George LW; Witkowski, Ed TF
We propose the use of archetypes as a way of moving between conceptual framings, empirical observations and the dichotomous classification rules upon which maps are based. An archetype is a conceptualisation of an entire category or class of objects. Archetypes can be framed as abstract exemplars of classes, conceptual models linking form and process and/or tacit mental models similar to those used by field scientists to identify and describe landforms, soils and/or units of vegetation. Archetypes can be existing taxonomic or landscape units or may involve new combinations of landscape attributes developed for a specific purpose. As landscapes themselves defy precise categorisation, archetypes, as considered here, are deliberately vague, and are described in general terms rather than in terms of the details that characterise a particular instance of a class. An example outlining the use of archetypes for landscape classification and mapping is demonstrated for granitic catenas in Kruger National Park, South Africa. Some 81% of the study area can be described in terms of archetypal catenal elements. However, spatial clustering of two classes that did not correspond to the archetypes prompted development of new archetypes. We show how the archetypes encoded in the map can be used to frame further knowledge in an ongoing, iterative and adaptive process. Building on this, we reflect on the value of vagueness in conservation science and management, highlighting how archetypes that are used to interpret and map landscapes may be better employed in the future.